2022
DOI: 10.3390/foods11213365
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Husk Scald Browning during Storage: A Review on Factors Involved, Their Modes of Action, and Its Association to Postharvest Treatments

Abstract: The pomegranate (Punica granatum L.), which contains high levels of health-promoting compounds, has received much attention in recent decades. Fruit storage potential ranges from 3 to 4 months in air and from 4 to 6 months in Controlled Atmospheres (CA) with 3–5% oxygen and 10–15% carbon dioxide. Storage life is limited by decay, chilling injury, weight loss (WL), and husk scald. In particular, husk scald (HS) limits pomegranate long-term storage at favorable temperatures. HS appears as skin browning which exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 101 publications
(133 reference statements)
1
16
0
Order By: Relevance
“… Integral model linking pre-harvest and harvest factors and its effects on chilling injury (CI) development during postharvest storage of pomegranate fruit. This integrative approach based on studies reported in the literature (see Section 3.1 and Section 3.2 ) can be used as a reference for identifying and introducing future studies on pre-harvest and harvest factors and also dissect their effects on different pomegranate fruit quality attributes and physiological disorders besides CI (e.g., husk scald effects [ 17 ]. Accordingly, chemical treatments (e.g., MeJa, ASA, salicylic acid, arginine), fruit variety, fruit maturity, shade, and irrigation will affect quality attributes (e.g., soluble solids, aril color, antioxidant enzymes, polyphenols) and reduce or favor chilling injury symptoms.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“… Integral model linking pre-harvest and harvest factors and its effects on chilling injury (CI) development during postharvest storage of pomegranate fruit. This integrative approach based on studies reported in the literature (see Section 3.1 and Section 3.2 ) can be used as a reference for identifying and introducing future studies on pre-harvest and harvest factors and also dissect their effects on different pomegranate fruit quality attributes and physiological disorders besides CI (e.g., husk scald effects [ 17 ]. Accordingly, chemical treatments (e.g., MeJa, ASA, salicylic acid, arginine), fruit variety, fruit maturity, shade, and irrigation will affect quality attributes (e.g., soluble solids, aril color, antioxidant enzymes, polyphenols) and reduce or favor chilling injury symptoms.…”
Section: Figurementioning
confidence: 99%
“…Proposed hypothetical model is based on references from Section 3.3 . Proposed model could be the basis of a hurdle strategy combining different technologies to attenuate CI in a similar fashion as previously described for husk scald disorder in pomegranate fruit [ 17 ].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Although browning increases under 5 • C, storage at low temperatures is necessary [6]. Symptoms of peel browning include pitting, husk scald, some softening, a higher sensitivity to decay, internal seed discoloration, and browning of chilling injury in postharvest pomegranate fruit during low-temperature storage [29,33,35]. We observed peel browning in the three soft-seed pomegranate fruit ('Mollar', 'Malisi', and 'Tunisian soft seed') from 30-45 d and in the two semi-soft-seed fruit ('Moyuruanzi' and 'Dongyan') from 60 d after the low-temperature storage.…”
Section: Peel Browningmentioning
confidence: 99%